The Effect of Profitability, Asset Structure, Growth, Liquidity and Debt Tax Shield on Capital Structure in Real Estate and Property Companies Listed on the Indonesia Stock Exchange: English - Calista; Yanuar Dananjaya (International Journal of Economics Accounting and Management, 2025)
growth, liquidity, and debt tax shield on capital structure in real estate and property companies listed on the Indonesia Stock Exchange. The study is motivated by the importance of determining an optimal capital structure to meet operational needs, maximize profits, and manage financial risks. Using the Pecking Order and Trade-Off theories, this research explains how these variables influence corporate financing decisions.  The population in this study consists of all real estate and property companies listed on the Indonesia Stock Exchange from 2019 to 2023. The data used are financial statements of companies selected through purposive sampling, resulting in 52 real estate and property companies as the research sample.  The results show that profitability, asset structure, and liquidity have a negative effect on capital structure, while growth and debt tax shield do not have a significant effect. Simultaneously, profitability, asset structure, growth, liquidity, and debt tax shield significantly affect capital structure. This study contributes theoretically to financial management literature and provides practical implications for financial managers and investors in making funding and investment decisions